Introduction to Anthropology - Hasty, Jennifer; Lewis, David G.; Snipes, Marjorie M. (Open textbook library., 2022)
Designed to meet the scope and sequence of your course, OpenStax Introduction to Anthropology is a four-field text integrating diverse voices, engaging field activities, and meaningful themes like Indigenous experiences and social inequality to engage students and enrich learning. The text showcases the historical context of the discipline, with a strong focus on anthropology as a living and evolving field. There is significant discussion of recent efforts to make the field more diverse—in its practitioners, in the questions it asks, and in the applications of anthropological research to address contemporary challenges. In addressing social inequality, the text drives readers to consider the rise and impact of social inequalities based on forms of identity and difference (such as gender, ethnicity, race, and class) as well as oppression and discrimination. The contributors to and dangers of socioeconomic inequality are fully addressed, and the role of inequality in social dysfunction, disruption, and change is noted.